The Military Museum As Classroom - Votaw, John (Teaching History: A Journal of Methods, 1994)
One of the difficult associations that students must make in their study of history is visualizing the physical conditions of the event or period under study. For example, when World War I pops up on the schedule of a history of Western civilization course, or a more specialized course in European, American, or World history, students might have difficulty in conjuring up images of what it must have been like for soldiers engaged in battle on the Western Front. It is easy to understand mud and stagnant water if you're standing in it up to your hips. But to imagine it without the "props" is harder. When we add the pictures of some of the other pervasive realities of combat in 1918-such as the unavoidable stench of death in the trenches, the crackle of machine gun fire, the ominous poison gas clouds hanging in shell craters, and the loud thumps of mortar and artillery rounds falling amongst frightened soldiers-the approximation of reality becomes more vivid. The problem for students is that they do not have a personal frame of reference with which to measure their new information.